Diagnosis and treatment of odontogenic cutaneous sinus tracts of endodontic origin: A case report - Peyman pour, Payam; Ashraf, Hengameh; Darmiani, Soheila (International Journal of Dental Research, 2013)
Aim: To describe a case of extra-oral sinus tract, related to infected tooth, which was initially misdiagnosed as skin lesion and inappropriately treated. Summary: The extra-oral sinus tract was initially misdiagnosed as skin lesion. Dermatological treatment was performed and antibiotics prescribed but the lesion did not resolve. Then, a dental cause was identified. Endodontic intervention resulted in resolution of the problem, confirming the initial misdiagnosis. Keywords: endodontic therapy, odontogenic fistula, sinus tract.